Tribo-corrosion study of nickel-free, high nitrogen and high manganese austenitic stainless steel. (March 2018) - Vats, Vishal; Baskaran, T.; Arya, Shashi Bhushan
Abstract: The electrochemical corrosion and tribo-corrosion behaviors of nickel-free high nitrogen (HN SS) and high manganese containing austenitic stainless steel were studied in simulated body fluids such as Ringer's and artificial saliva solutions (ASS) using tribo-meter attached with the potentiostat. Type 316L SS used as reference alloy for comparison. Open circuit potential (OCP) and potentiodynamic polarization techniques were used to examine the passivation and corrosion behavior of both the stainless steels under the applied loads of 5 and 10 N at room temperature and also compared with the static condition of corrosion. Pitting resistance of HN SS was found to be significantly higher over type 316L SS. Highlights: Tribocorrosion study was carried out at three different load and fixed rpm using tribocorrosion steup. Free corrosion potential increased negatively with increase in loads. A stable passivation behaviour and very passive current density was found for high nitrogen nickel free stainless steel as compared to reference alloy (type 316 SS) in artificial physiological solutions.